GPRC6A: Jack of all metabolism (or master of none) - Min Pi; Satoru Kenneth Nishimoto; L. Darryl Quarles (Elsevier, 2017)
Background: GPRC6A, a widely expressed G-protein coupled receptor, is proposed to be a master regulator of complex endocrine networks and metabolic processes. GPRC6A is activated by multiple ligands, including osteocalcin (Ocn), testosterone (T), basic amino acids, and various cations. Scope of Review: We review the controversy surrounding GPRC6A functions. In mice, GPRC6A is proposed to integrate metabolic functions through the coordinated secretion of hormones, including insulin, GLP-1, T, and IL-6, and direct effects of this receptor to control glucose and fat metabolism in the liver, skeletal muscle, and fat. Loss-of-GPRC6A results in metabolic syndrome (MetS), and activation of GPRC6A stimulates proliferation of β-cells, increases peripheral insulin sensitivity, and protects against high fat diet (HFD) induced metabolic abnormalities in most mouse models. Bone, cardiovascular, immune, and skin functions of GPRC6A have also been identified in mice. Expression of GPRC6A is increased in prostate cancer (PCa) cells, and inhibition of GPRC6A attenuates PCa progression in mouse models. The function of GPRC6A in humans, however, is not clear. During evolution, a unique polymorphism of GPRC6A emerged mainly in humans of Asian and European decent that has been proposed to alter membrane trafficking and function. In contrast, the ancestral allele found in all other species is retained in 1%, 15%, and 40% of people of Asian, European and African descent, respectively, suggesting GPRC6A gene variants may contribute to the racial disparities in the risk of developing MetS and PCa. Major Conclusions: If the regulatory functions of GPRC6A identified in mice translate to humans, and polymorphisms in GPRC6A are found to predict racial disparities in human diseases, GPRC6A may be a new gene target to predict, prevent, and treat MetS, PCa, and other disorders impacted by GPRC6A. Keywords: GPCR, Racial disparities, Prostate cancer, Type 2 diabetes, Membrane trafficking, Osteocalcin, Testosterone, Gene polymorphisms